PENGARUH KUALITAS SISTEM INFORMASI DAN PENGETAHUAN AKUNTANSI TERHADAP KUALITAS INFORMASI AKUNTANSI - Lestari, Agustina Dwi; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to examine the influence quality of computerized information system and theaccounting knowledge to the quality of accounting information which is done by using perceived ease of use asthe intervening variable. The data analysis has been done by using regression analysis with the causal stepmethod which has been developed by Baron and Keny (1986). The independent variables are: the quality ofinformation system (KSI), and the accounting knowledge (PA), the dependent variable are: the quality ofaccounting information (KIA), and the intervening variable: perceived ease of use.The result of the researchshows that directly the quality of information system and also the accounting knowledge variablessimultaneously do not have any significant influence to the quality of accounting information. Indirectly thequality of computerized information system and also acounting knowledge simultaneously has significantinfluence to the quality of accounting infrmation through perceived ease of use. The perceived ease of use variableis proven as the intervening variable which is shown by the regression model 3 on t test shows that theindependent variable of quality of information system and accounting knowledge do not have any significantinfluence when the simultaneous test has been done by using perceived ease of use variable.Keywords: System of Accounting Information, Accounting Knowledge, Perceived ease of use, Quality ofAccounting Information.